Post-synthesis functionalization of a zeolitic imidazolate structure ZIF-90: a study on removal of Hg(ii) from water and epoxidation of alkenes. Issue 12 (28th March 2015) - Bhattacharjee, Samiran; Lee, Yu-Ri; Ahn, Wha-Seung
<x xml:space="preserve">Abstract</x> Thiol-functionalized ZIF-90 (ZIF-90-SH) and its Mn(ii)-immobilized form (ZIF-90-S[Mn]) were prepared. The former exhibited an Hg2+ adsorption capacity of ca. 22.4 mg g−1 at room temperature and ZIF-90-S[Mn] showed good catalytic performance in the epoxidation of several important alkenes using molecular oxygen under atmospheric pressure.